Activation of host transient receptor potential (TRP) channels by praziquantel stereoisomers - Gunaratne, Gihan S.; Yahya, Nawal A.; Dosa, Peter I.; Marchant, Jonathan S. (PLOS Neglected Tropical Diseases, 2018)
Author summary Praziquantel is a key drug for combating diseases caused by parasitic flatworms. It is the therapeutic mainstay for treatment of schistosomiasis, a disease that afflicts over 200 million people worldwide. In this study, we investigate potential molecular targets of praziquantel, and demonstrate interactions with several members of the transient receptor potential (TRP) ion channel family over the micromolar range. These interactions with endogenous host TRP channels may contribute to regulation of vascular contractility in the blood vessels where the mature parasites reside.